Pengaruh penerapan permainan tradisional bebentengan dan lari balok terhadap percaya diri siswa SMK Kiansantang kota bandung - Heru sulistiadinata; Dedi Kurnia; Beny Nur Arifin (Journal of Physical and Outdoor Education, 2022)
In this study, the problem that will be discussed is about the self-confidence of the students of SMK Kiansantang, Bandung City. Objective: To find out whether there is a significant effect on the application of traditional games fortifications and beam running on the self-confidence of the students of SMK Kiansantang, Bandung City. The benefits of this research are that theoretically it can be used as information and meaningful scientific contributions for formal, non-formal, and informal educational institutions. The method used is the experimental method, which is the development of science and technology in order to produce a product that can be enjoyed by the public safely. The population in this study were students of SMK Kiansantang, Bandung City. The sample used amounted to 27 people with data collection techniques Cluster Sampling (Area Sampling). The instrument used is in the form of a questionnaire with the number of questions used is 35 questions with instrument reliability of 0.893. The results of the significance level test show that the known value of Sig. (2-tailed) of 0.000 is smaller than <0.05, it can be concluded that H1 is accepted and Ho is rejected. This means that there is a significant influence on the application of traditional games fortifications and beam running on the confidence ofKiansantangHigh School students in Bandung. The result of data processing is the percentage of self-confidence 91.78%, with sub-variables belief in self-ability 82.96%, optimistic 92.59%, objective 90.33%, and responsible 91.85%, rational and realistic 89, 38%. The conclusion of this study is that there is a high influence of the application of traditional games fortification and beam running on the self-confidence of the students of SMK Kiansantang, Bandung City.